Consolidated Vacuum Corporation Model 2001 Masschromatograph - Consolidated Vacuum Corporation; Bendix Corporation (1973)
Close-up view of a portion of a Consolidated Vacuum Corporation Model 2001 Masschromatograph, with view of the exposed interior showing a CTI-Cryogenics high vacuum pump. Also known as CVC Products Inc., Consolidated Vacuum Corporation operated as a subsidiary of the Bendix Corporation prior to Allied Signal's takeover of Bendix in 1983. The Masschromatograph 2001 offered the qualitative and quantitative capabilities of combined gas chromatography and mass spectrometry for a variety of laboratory applications, including forensics, toxicology, and food flavoring.
Keywords: Scientific apparatus and instruments; Consolidated Vacuum Corporation; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Gas chromatography; Bendix Corporation; Gas chromatography--Instruments; Mass spectrometers